Does search engine query data contribute to returns and liquidity? - Nurazi, Ridwan; Usman, Berto (Serbian Journal of Management, 2019)
This study attempts to identify the impact of investor’s attention which is surrogated by the search engine query data on the internet using Google on returns and liquidity. The data used in this study is extracted from Google Trend data set, and hand-collected data from the Indonesia Capital Market Directory (ICMD). By employing panel data analysis, our results show that search engine query data (information retrieval) by using the internet (Google) is clearly an important method of attenuating the level of asymmetry information between the informed and un-informed investors. Moreover, the utilization of microeconomic factors such as financial or non-financial information that can be easily obtained from the annual reports are strongly useful in helping investors preparing their portfolio of investment. Meanwhile, the macroeconomics factors such as inflation, interest rate, exchange rate, and GDP are the country-level effect which results in either positive or negative impact on returns and liquidity. By employing 83 samples and six years time period of observation, we infer that information retrieval through the search engine query data on the internet, macroeconomics factors and microeconomics factors are strongly and significantly related to returns and liquidity in the Indonesia stock exchange.